Analysis of The Quality Management Information Systems and Work Environment on Performance in Islamic Perspective - Destiana Kumala; HM Usman (Sharia Business Management Department of STEBIS Bina Mandiri, 2022)
Employee performance in an organization can be influenced by several factors, one of which is management information systems and the work environment. The method used in this study is the Structural Equation Modeling (SEM) Partial Least Square (PLS), based on variance so that the analysis of two factor conditions cannot be determined and the conditions in which the solution cannot be accepted. This type of research uses purposive sampling technique, namely by using primary data from the results of filling out the questionnaire, which analyzes SEM where the data used does not have to have a normal multivariate distribution. Measurements made with the Outner Model and Inner Model. results Based on the research, the results of research on employees of the Production Division at PT. Megah Megalon Industries shows that the study of the Management Information System variable (X1) and the Work Environment variable (X2) with their indicators affects the Employee Performance variable (Y) with the indicators significantly